Memory of Ensemble Representation Was Independent of Attention - Peng, Shenli; Kuang, BeiBei; Hu, Ping (Frontiers in Psychology, 2019)
The hierarchical view of working memory suggested that object ensemble could be also stored into working memory by treating ensemble properties as single “unit”. However, it remains unclear whether ensemble representation in working memory is vulnerable to attention demanding. The present study designed a dual-task paradigm constituting of a memory retaining task and an attention-demanding arrow flanker task. Participants were firstly presented an array (4 or 9) of facial images with neutral expressions, and then shown a left- or right-orientated arrow surrounded by four congruent or incongruent oriented arrows, or short lines. Participants judged the orientation of the target arrow, and then indicated whether a probe facial image was present or absent in the preceding facial array. The probe face consisted of four conditions: (a) a morphed average face of prior face set, (b) a morphed average face of another face set, (c) an exemplar face of prior set, and (d) an exemplar face of another face set. Results confirmed that participants implicitly coded the average facial image of preceding set and retained in working memory. More importantly, the memory representation of ensemble property (e.g. average facial identity) was independent of flanker type. In sum, this study provided further evidence of the hierarchical view of working memory, and suggested that attention was not a pre-requisite for the retaining of ensemble properties in working memory.